Investigations on electrical conducting magnetic hybrid materials for sensor and actuator systems - Chávez Vega, Jhohan Harvey (2016)
Scientists and engineers feel motivated in the presence of new elements or materials they cannot comprehend. That is why when a material with a new properties or behavior arises, they do the best to investigate on them until understand them and give some applications. One of these kind of moderns materials are the ferrofluids, which have a special and very different behavior when are induced under magnetic field and when not. These materials have plenty of applications nowadays. Due to their smart behaviour they are used on dampers for automobile suspensions, for measurement of fluid’s viscosities, acoustics and several more tasks. Magneto sensible elastomers (MSE) are materials that own similar properties to ferrofluids, with the substantial difference of being in solid state independently of the presence or absence of magnetic field. MSE are composed on a polymer matrix that has magnetic particles that provide them a smart behaviour under magnetic fields. For this project the magnetic particles were iron powder and certain amounts of graphite were also added to give electrical conductivity. In the current work it was fabricated several samples of MSE to study the behaviour of their electrical and mechanical properties under the effect of a magnetic field. Permanent magnets were used to induce the magnetic field on the probes and this field was changed by moving the magnets away and close to the probes through a motorized positioning machine. The results obtained from the experiments are summarized on conclusions that can be used in future to the design and building of sensors and actuators.